Exploring Digital Design Multi-Disciplinary Design Practices - Wagner, Ina.; Bratteteig, Tone.; Stuedahl, Dagny. (Computer Supported Cooperative Work,, 2010)
Exploring Digital Design takes a multi-disciplinary look at digital design research where digital design is embedded in a larger socio-cultural context. Working from socio-technical research areas such as Participatory Design (PD), Computer Supported Cooperative Work (CSCW) and Human-Computer Interaction (HCI), the book explores how humanities offer new insights into digital design, and discusses a variety of digital design research practices, methods, and theoretical approaches spanning established disciplinary borders. The aim of the book is to explore the diversity of contemporary digital design practices in which commonly shared aspects are interpreted and integrated into different disciplinary and interdisciplinary conversations. It is the conversations and explorations with humanities that further distinguish this book within digital design research. Illustrated with real examples from digital design research practices from a variety of research projects and from a broad range of contexts Exploring Digital Design offers a basis for understanding the disciplinary roots as well as the interdisciplinary dialogues in digital design research, providing theoretical, empirical, and methodological sources for understanding digital design research. The first half of the book Exploring Digital Design is authored as a multi-disciplinary approach to digital design research, and represents novel perspectives and analyses in this research. The contributors are Gunnar Liestl̜, Andrew Morrison and Christina Mr̲tberg in addition to the editors. Although primarily written for researchers and graduate students, digital design practioners will also find the book useful. Overall, Exploring Digital Design provides an excellent introduction to, and resource for, research into digital design.